Retinal Hypercholesterolemia Triggers Cholesterol Accumulation and Esterification in Photoreceptor Cells - Saadane, Aicha (J Biol Chem, 2016)
The process of vision is impossible without the photoreceptor cells, which have a unique structure and specific maintenance of cholesterol. Herein we report on the previously unrecognized cholesterol-related pathway in the retina discovered during follow-up characterizations of Cyp27a1(−/−)Cyp46a1(−/−) mice. These animals have retinal hypercholesterolemia and convert excess retinal cholesterol into cholesterol esters, normally present in the retina in very small amounts. We established that in the Cyp27a1(−/−)Cyp46a1(−/−) retina, cholesterol esters are generated by and accumulate in the photoreceptor outer segments (OS), which is the retinal layer with the lowest cholesterol content. Mouse OS were also found to express the cholesterol-esterifying enzyme acyl-coenzyme A:cholesterol acyltransferase (ACAT1), but not lecithin-cholesterol acyltransferase (LCAT), and to differ from humans in retinal expression of ACAT1. Nevertheless, cholesterol esters were discovered to be abundant in human OS. We suggest a mechanism for cholesterol ester accumulation in the OS and that activity impairment of ACAT1 in humans may underlie the development of subretinal drusenoid deposits, a hallmark of age-related macular degeneration, which is a common blinding disease. We generated Cyp27a1(−/−)Cyp46a1(−/−)Acat1(−/−) mice, characterized their retina by different imaging modalities, and confirmed that unesterified cholesterol does accumulate in their OS and that there is photoreceptor apoptosis and OS degeneration in this line. Our results provide insights into the retinal response to local hypercholesterolemia and the retinal significance of cholesterol esterification, which could be cell-specific and both beneficial and detrimental for retinal structure and function.